2020
DOI: 10.1097/mjt.0000000000001196
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Avoiding Ibuprofen. How Good Is the Evidence?

Abstract: Ibuprofen is an over-the-counter medication that is used widely for the treatment of pain and fever during COVID-19 pandemic. A concern was raised regarding the safety of ibuprofen use because of its role in increasing ACE2 levels within the Renin-Angiotensin-Aldosterone system. ACE2 is the coreceptor for the entry of SARS-CoV-2 into cells, and so, a potential increased risk of contracting COVID-19 disease and/or worsening of COVID-19 infection was feared with ibuprofen use. However, available data from limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 16 publications
0
29
1
1
Order By: Relevance
“…The PockDrug-Server was used applying the Fpocket method. reported to be concentration dependent and may require up to 0.500 M [24]. Additionally, it has been pointed out that in the case of NSAIDs the molecular docking values can be much closer to the selectivity through energy terms, but not to the IC 50 , and it has been indicated that for these compounds the molecular docking represents the descriptor most important for drug-protein interactions [82].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PockDrug-Server was used applying the Fpocket method. reported to be concentration dependent and may require up to 0.500 M [24]. Additionally, it has been pointed out that in the case of NSAIDs the molecular docking values can be much closer to the selectivity through energy terms, but not to the IC 50 , and it has been indicated that for these compounds the molecular docking represents the descriptor most important for drug-protein interactions [82].…”
Section: Discussionmentioning
confidence: 99%
“…However, this statement, although it contributes to the described use of NSAIDs for the empirical treatment and prevention of COVID-19 [93], requires its experimental demonstration because our predictions cannot guarantee a pharmacologically and clinically relevant interaction. Therefore, more studies are needed, especially given the real controversy that exists regarding the use of these drugs against COVID-19 [19][20][21][22][23][24][25][26][27]. Especially because to date, only one theoretical report of a binding of ligand at the interface of the RBD-ACE2 complex is known [49,50], but this binding is in a different region than the one found in this work, in our work the binding of Ibuprofen occurs in an allosteric region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies are accumulating and reappraising the importance of NSAIDs in COVID-19 management (Bruce et al, 2020;Kutti Sridharan et al, 2020;Smart and Fawkes, 2020;Zolk et al, 2020); interestingly two in silico screenings independently identified the COX-II inhibitor celecoxib as a potential anti-SARS-CoV-2 drug, and a very recent study still under peer review reports its beneficial effects plus famotidine in hospitalized patients (Tomera et al, 2020).…”
Section: Nsaids Paracetamol and Covid-19mentioning
confidence: 99%
“…At this point, there exist no scientific data to support an increased risk of SARS-CoV-2 infection or COVID-19 severity with ibuprofen. As for chloroquine [45], it is certainly time for a properly conducted study of the potential risks and benefits of ibuprofen in COVID-19 [46,47].…”
mentioning
confidence: 99%